Income Poverty and Well-Being - Rojas, Mariano (Springer Link, 2024)
High income inequality in Latin America translates into high poverty rates in many countries. Those in income poverty report lower well-being; however, the well-being impact of income poverty is not generalized across domains of life. Satisfaction in some important domains of life, such as the family and the affective ones, are not affected by people’s material condition, and this implies for a not so strong association between income poverty and well-being deprivation. Thus, it is important for policy makers to expand their perspective in order to go beyond the limited income-poverty conception and incorporate other well-being considerations in poverty-abatement programs.
Keywords: income poverty; well-being; Latin America; WOS(2)